Exploring the Nutritional and Sensory Impact of Red Seaweed Fortification in Dark Chocolate: Red Seaweed Fortified Dark Chocolate - Debbarma, Jesmi; S., Sireesha; S., Remya; P., Viji; B., Madhusudana Rao (Fishery Technology, 2024)
The present study was aimed to develop seaweed-based chocolates and evaluate their nutritional, textural and sensory properties. Seaweed powder prepared from the red seaweeds Gracilaria edulis and Kappaphycus alvarezii was added separately to dark chocolate at different concentrations of 1%, 2.5%, 5%, and 7.5% (w/w) and stored under chilled condition (2-4˚°C) for further studies. Incorporation of seaweed in chocolate improved the protein and mineral content in the products. The addition of seaweed significantly (p<0.05) increased the breaking strength of the chocolate, with the force required to break the chocolate increasing proportionally with the seaweed concentration. Chocolate enriched with K. alvarezii exhibited significantly (p<0.05) lower breaking strength compared to chocolate enriched with G. edulis. Chocolate enriched with 1% and 2.5% K. alvarezii had similar hardness and chewiness of that of control chocolate. Sensory evaluation revealed that chocolate containing up to 7.5% red seaweed was deemed acceptable, with no detectable seaweed smell. The flavour of the dark chocolate effectively masked the seaweed flavour and odour. Moreover, organoleptic acceptance was significantly higher (p<0.05) for chocolate enriched with K. alvarezii as compared to chocolate enriched with G. edulis. Results shows that red seaweed such as G. edulis and K. alvarezii can be considered as a potential ingredient for formulating healthy confectionery products without affecting consumer acceptance.